Prediction of Scapular Dyskinesis Through Electromyographic Indices of Scapulothoracic Muscles in Female Overhead Athletes - Leila Ghanbari; Mohammad Hossein Alizadeh; Hooman Minoonejad; Seyed Hossein Hosseini (Shiraz University of Medical Sciences, 2018)
Background: Shoulder joint function and the athletic performance of overhead athletes are influenced by scapular dyskinesis (SD) due to its high prevalence among these athletes and the motor interaction between the scapula and the arm. The present study investigated the prediction of SD through the electromyographic indices of scapulothoracic muscles in female overhead athletes. Methods: The present descriptive-correlational study was carried out on 60 female volleyball, handball, basketball, and badminton athletes. The lateral scapular slide test was used to examine their SD. The required electromyography and electrogoniometry data was recorded simultaneously to measure the activity and onset time of scapulothoracic muscles, including upper trapezius (UT), lower trapezius (LT), and serratus anterior (SA). The collected data was analyzed using Spearman correlation and multiple regression tests. Results: Significant correlations were found between all electromyographic variables and SD (P<0.01). The regression effects of all predictive variables on SD were significant (P=0.001). In terms of predictive power, UT/SA co-contraction (β=0.765), UT/LT co-contraction (β=0.716), LT onset time (β=0.672), LT activity (β=0.612), and SA onset time (β=0.576) had the highest regression effects on SD, respectively. The analysis of the study model showed that there was a strong correlation (r=0.694) between the predictive variables and SD and that the independent variables predicted 48% of the variance. Conclusion: The presence of imbalance in the scapulothoracic muscles of overhead athletes with SD indicates that athletes should be monitored by coaches, physiotherapists, and physicians for SD screening. It is also necessary to carry out prospective studies to examine and explore other variables related to SD.